Invisible capital : how unseen forces shape entrepreneurial opportunity - Rabb, Chris (BK currents book., 2010)
Writer, consultant and speaker Chris Rabb coined the term "invisible capital" to represent the unseen forces that dramatically impact entrepreneurial viability when a good attitude, a great idea, and hard work simply aren't enough. In his book, Invisible Capital: How Unseen Forces Shape Entrepreneurial Opportunity, Rabb puts forth concrete and effective ways entrepreneurs and their advocates can build and grow sustainable enterprises amid these unseen forces created by society's uneven playing field. By honoring democratic ideals, challenging assumptions, and reframing how success is defined, Ra.